Lymphoplasmacytic lymphoma with paraprotein IgG - Mat Yusuf, Shaidatina; Mohd Tohit, Eusni Rahayu; Nahanthiran, Subithira (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Lymphoplasmacytic lymphoma (LPL) is a rare indolent mature B-cell lymphoma. LPL secreting immunoglobulins other than IgM are rare. There are very few case series on non-IgM LPL, and little is known about the clinical features and outcomes of patients with this disease. We report the case of a 65-year-old-male who was referred to our hospital for further investigations of persistent chronic anaemia and was diagnosed with IgG-LPL based on the presence of M protein from serum electrophoresis. Bone marrow morphology exhibit a spectrum of B-cell differentiation ranging from small mature lymphocytes to plasma cells. The patient underwent treatment with a combination of bortezomib, dexamethasone and rituximab and showed positive response. LPL with paraprotein IgG is a rare indolent disease and has a heterogeneous clinicopathological presentation with limited literature reviews. Our case report and literature review provide insights and knowledge in the description of the clinicopathological features of IgG LPL.